Early-Career Teachers Living on School Landscapes Shaped by Equity Policies and Practices: Helena’s and Kristin’s Stories - Ross, Vicki Dea; Chaseley, Tina; Mocanu, R. Gabriela; Zhang, Yuanyibo (Frontiers in Education, 2022)
Before moving beyond the beginning stages of becoming a teacher, one of every two teachers leaves the profession. Hence, for several decades, the recruitment, development, and retention of teachers has been a pernicious problem facing districts, schools, administrators, and school personnel. A productive line of narrative inquiry research has focused on teacher education and development. Additionally, narrative inquiries have focused on teacher retention and attrition. For example, several researchers have narratively inquired into the processes of transitioning out of the profession. In the present investigation, we asked an overarching question, what do beginning teachers need in order to tell stories of staying? And, relatedly, in schools working toward addressing questions of equity, what are the experiences of early-career teachers? And, what can be done to develop and sustain them in their professional commitments? Two novice teachers, Helena and Kristin, both of whom took initial positions in the same district, which had a commitment to promoting equity for children, were interviewed to gather perspectives on their early-career experiences. Both participants shared tension-filled stories from their beginning years as a teacher that created a sense of disequilibrium connected to their developing sense of self. The data analysis pointed to the value that the concept of the best-loved self may have in helping teachers construct their sense of identity. As in the case of Helena and Kristin, this sense of the best-loved self may develop early and can shift over time. For teacher educators, this aspect provides an opening for exploring philosophical commitments within preparations programs with teacher candidates. For teachers and administrators in schools who are intaking beginning teachers, understanding these nascent facets of best-loved teacher self may provide a window into these novice teachers’ motivations. And, these practices may prompt the reconnection to philosophical commitments and aspirations in the day-to-day tug at the fabric of teacher identity.